2002
DOI: 10.1046/j.1445-2197.2002.02295.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent torsion after previous testicular fixation

Abstract: The higher incidence of recurrent torsion after fixation using absorbable rather than non-absorbable sutures in the literature may be caused by a greater number of fixations being carried out using absorbable suture. Use of non-absorbable suture is limited by the high rate of abscess formation. The most important factor for adhesion formation would appear to be the eversion of the tunica vaginalis and it is recommended that this is carried out at all testicular fixations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
(18 reference statements)
0
28
0
5
Order By: Relevance
“…However, the use of nonabsorbable suture is limited because it is associated with a high rate of abscess formation. Hence, it has been suggested that the most important factor for adhesion formation would appear to be the eversion of the tunica vaginalis, and it is recommended that this is carried out at all testicular fixations (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of nonabsorbable suture is limited because it is associated with a high rate of abscess formation. Hence, it has been suggested that the most important factor for adhesion formation would appear to be the eversion of the tunica vaginalis, and it is recommended that this is carried out at all testicular fixations (23).…”
Section: Discussionmentioning
confidence: 99%
“…11 A subsequent study by Mor et al identified a recurrence rate of 4%, occurring 6 months to 23 years following orchiopexy. 11 A subsequent study by Mor et al identified a recurrence rate of 4%, occurring 6 months to 23 years following orchiopexy.…”
Section: Discussionmentioning
confidence: 96%
“…Mushtaq et al described a return rate of 4% in those undergoing exploration, 38% of whom were metachronous, compared with 10% and 25% in our cohort, respectively. 7,8,11 Four and a half percent of boys in our centre re-presented following surgery with pain, swelling or redness deemed within normal post-operative limits, and were subsequently discharged with no intervention. 7 They described a re-exploration rate of 7.6% (64/840) over a 11-year period, with three of these boys each requiring three acute scrotal explorations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations